Beyond Dichotomy Synergizing Writing Center and Classroom Pedagogies - Corbett, Steven J. (Open textbook library., 2015)
How closely can or should writing centers and writing classrooms collaborate? Beyond Dichotomy explores how research on peer tutoring one-to-one and in small groups can inform our work with students in writing centers and other tutoring programs, as well as in writing courses and classrooms. These multi-method (including rhetorical and discourse analyses and ethnographic and case-study) investigations center on several course-based tutoring (CBT) partnerships at two universities. Rather than practice separately in the center or in the classroom, rather than seeing teacher here and tutor there and student over there, CBT asks all participants in the dynamic drama of teaching and learning to consider the many possible means of connecting synergistically. This book offers the "more-is-more" value of designing more peer-to-peer learning situations for developmental and multicultural writers, and a more elaborate view of what happens in these peer-centered learning environments. It offers important implications—especially of directive and nondirective tutoring strategies and methods—for peer-to-peer learning and one-to-one tutoring and conferencing for all teachers and learners of writing.